Oceanographic Variability Induced by Tides, the Intraseasonal Cycle and Warm Subsurface Water Intrusions in Maxwell Bay, King George Island (West-Antarctica) - Cordero-Carrasco, R; Llanillo, P (Nature Research, 2019)
We examine the hydrographic variability induced by tides, winds, and the advance of the austral summer, in Maxwell Bay and tributary fjords, based on two recent oceanographic campaigns. We provide the first description in this area of the intrusion of relatively warm subsurface waters, which have led elsewhere in Antarctica to ice-shelf disintegration and tidewater glacier retreat. During flood tide, meltwater was found to accumulate toward the head of Maxwell Bay, freshening and warming the upper 70 m. Below 70 m, the flood tide enhances the intrusion and mixing of relatively warm modified Upper Circumpolar Deep Water (m-UCDW). Tidal stirring progressively erodes the remnants of Winter Waters found at the bottom of Marian Cove. There is a buoyancy gain through warming and freshening as the summer advances. In Maxwell Bay, the upper 105 m were 0.79 °C warmer and 0.039 PSU fresher in February than in December, changes that cannot be explained by tidal or wind-driven processes. The episodic intrusion of m-UCDW into Maxwell Bay leads to interleaving and eventually to warming, salinification and deoxygenation between 80 and 200 m, with important implications for biological productivity and for the mass balance of tidewater glaciers in the area. © 2019, The Author(s).